A Test for the Assessment of Pragmatic Abilities and Cognitive Substrates (APACS): Normative Data and Psychometric Properties - Arcara, Giorgio; Bambini, Valentina (Frontiers in Psychology, 2016)
The Assessment of Pragmatic Abilities and Cognitive Substrates (APACS) test is a new tool to evaluate pragmatic abilities in patients with acquired communicative deficits, ranging from schizophrenia to neurodegenerative diseases. APACS focuses on two main domains, namely discourse and non-literal language, combining traditional tasks with refined linguistic materials in Italian, in a unified framework inspired by language pragmatics. The test includes six tasks (Interview, Description, Narratives, Figurative Language 1, Humor, Figurative Language 2) and three composite scores (Pragmatic Productions, Pragmatic Comprehension, APACS Total). Psychometric properties and normative data were computed on a sample of 119 healthy participants representative of the general population. The analysis revealed acceptable internal consistency and good test-retest reliability for almost every APACS task, suggesting that items are coherent and performance is consistent over time. Factor analysis supports the validity of the test, revealing two factors possibly related to different facets and substrates of the pragmatic competence. Finally, excellent match between APACS items and scores and the pragmatic constructs measured in the test was evidenced by experts’ evaluation of content validity. The performance on APACS showed a general effect of demographic variables, with a negative effect of age and a positive effect of education. The norms were calculated by means of state-of-the-art regression methods. Overall, APACS is a valuable tool for the assessment of pragmatic deficits in verbal communication. The short duration and easiness of administration make the test especially suitable to use in clinical settings. In presenting APACS, we also aim at promoting the inclusion of pragmatics in the assessment practice, as a relevant dimension in defining the patient’s cognitive profile, given its vital role for communication and social interaction in daily life. The combined use of APACS with other neuropsychological tests could also improve our understanding of the cognitive substrates of pragmatic abilities and their breakdown.